RehabilitacjaPhysical activity, inflammatory factors and endothelial function among adult men with coronary artery disease - Nonas, Monika; Fornalczyk-Wachowska, Ewa; Śmigielski, Janusz; Jegier, Anna (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Background: Regular physical activity has a direct relation with the prevention of coronary artery disease. The basis of this effect has not been explicitly explained yet. Probably vascular endothelium is important in this relation. The main goal of the study was to determine the correlation between endothelial function, inflammatory state and physical efficiency and physical activity among men with coronary artery disease. Materials and methods: The study included 60 adult men with coronary artery disease, with the average age of 55.6±6.6 years, divided into two groups according to declared leisure time physical activity The border line was energy expenditure on physical activity at the level of 600 kcal/week. Physical activity assessment was carried out by the Seven Day Physical Activity Recall. Physical efficiency was characterized by metabolic equivalent (METs) achieved at the end of the submaximal exercise test. The endothelial function and the presence of inflammatory state were estimated by hsCRP, sICAM-1 and sE-sel ELISA serum assignment. Some selected risk factors of chronic cardiovascular and metabolic diseases were evaluated as well as basic anthropometric parameters. Results: Compared to physically inactive men with coronary artery disease, among men who are physically active there were observed lower, but without statistical significance, serum concentration of hs-CRP (2.9±2.1 vs 3.6±2.7 mg/l; p>0.05) and lack of differences in serum concentration of sICAM-1 (350.1±85.7 vs 338.6±58.8 ng/ml; p>0.05) and sE-sel (58.6±33.7 vs 57.2±25.7 ng/ml; p>0.05). There was no correlation between physical efficiency of men with coronary artery disease and serum concentrations of hsCRP, sICAM-1 and sE-sel (r=-0.08, p=0.67; r=-0.02, p=0.93; r=0.14, p=0.47 respectively). Conclusions: The study did not reveal that energy expenditure on regular physical effort ≥600 kcal/week was connected with significantly better function of endothelium and lower activity of inflammatory state, described by hs-CRP, sICAM-1 and sE-sel, among men with coronary artery disease.